2017
DOI: 10.1097/cej.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and colorectal cancer risk: a meta-analysis

Abstract: The analysis of dietary patterns has recently drawn considerable attention as a method of investigating the association between the overall whole diet and the risk of colorectal cancer. However, the results have yielded conflicting findings. Here, we carried out a meta-analysis to identify the association between dietary patterns and the risk of colorectal cancer. A total of 40 studies fulfilled the inclusion criteria and were included in this meta-analysis. The highest category of 'healthy' dietary pattern co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
63
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 64 publications
6
63
2
2
Order By: Relevance
“…Several systematic reviews and meta-analysis have recently reported the association between dietary patterns and risk of cancer in different sites such as breast [42], colon and rectum [43,44], stomach [45], esophagus and lung [46,47]. Similar to our results, in some meta-analysis it was found that the consumption of a Western dietary pattern was positively associated to an increment of cancer risk in the colon [43], colorectal and stomach [44,45].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Several systematic reviews and meta-analysis have recently reported the association between dietary patterns and risk of cancer in different sites such as breast [42], colon and rectum [43,44], stomach [45], esophagus and lung [46,47]. Similar to our results, in some meta-analysis it was found that the consumption of a Western dietary pattern was positively associated to an increment of cancer risk in the colon [43], colorectal and stomach [44,45].…”
Section: Discussionsupporting
confidence: 80%
“…Similar to our results, in some meta-analysis it was found that the consumption of a Western dietary pattern was positively associated to an increment of cancer risk in the colon [43], colorectal and stomach [44,45]. On the other hand, no significant correlation was evidenced for breast [42], rectal and esophagus cancers [43,46].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Several systematic reviews and meta-analyses have recently reported the association between dietary patterns and the risk of cancer in different sites; such as breast [42], colon and rectum [43,44], stomach [45], esophagus, and lung [46,47]. Similar to our results—in some of them, it was found that the consumption of a Western dietary pattern was positively associated to an increment of cancer risk in the colon [43] colorectal, and stomach [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the whole diet in the assessment of cancer risk is supported by several recent systematic review and meta-analysis which have considered the effects of dietary patterns instead of single components on CRC risk [80][81][82]. However, although dietary patterns representing a broader picture of food and nutrient consumption may be more predictive of disease risk, the meat type, the cooking methods and the meat doneness are further variables which vary between populations.…”
Section: Discussionmentioning
confidence: 99%